2002
DOI: 10.1007/s00018-002-8414-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic phospholipase A 2 and lipoxygenase are involved in cell cycle progression in neuroblastoma cells

Abstract: Arachidonic acid has been implicated in regulating cellular proliferation, and is preferentially released by the 85-kDa cytosolic phospholipase A2 (cPLA2). Recently, we demonstrated that cPLA2 is activated at distinct periods during the ongoing cell cycle of neuroblastoma cells. The purpose of the present study was to establish the role of these cPLA2 activity peaks in cell cycle progression. Inhibition of cPLA2 activity with arachidonyl trifluoromethylketone (ATK) in early G1 phase reduced DNA synthesis marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…We used these cell types because they yield relatively high numbers of mitotic cells and because we have thoroughly characterized cell cycle regulation from mitosis to S phase in both cell lines in previous studies (Hulleman et al, 1999a;Hulleman et al, 1999b;van Rossum et al, 2002). The experimental design is outlined schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used these cell types because they yield relatively high numbers of mitotic cells and because we have thoroughly characterized cell cycle regulation from mitosis to S phase in both cell lines in previous studies (Hulleman et al, 1999a;Hulleman et al, 1999b;van Rossum et al, 2002). The experimental design is outlined schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During these phases, elevations in cPLA 2 activity are due to increased phosphorylation rather than increased cPLA 2 protein expression. This suggestion is supported by studies in which phosphatase treatment of cPLA 2 reduces its activity [42]. The inhibition of cPLA 2 with arachidonyl trifluoromethylketone in early G1 phase markedly reduces DNA synthesis suggesting that cPLA 2 plays an important role in progression of the cell cycle.…”
Section: Nuclear Pla 2 Activitiesmentioning
confidence: 83%
“…The inhibition of cPLA 2 with arachidonyl trifluoromethylketone in early G1 phase markedly reduces DNA synthesis suggesting that cPLA 2 plays an important role in progression of the cell cycle. Cyclooxygenase inhibitors have no effect on cell cycle progression into S phase [42], indicating that the cPLA 2 -dependent progression is not mediated by arachidonic acid metabolites generated by cyclooxygenase. However, the lipoxygenase inhibitors caffeic acid and nordihydroguaiaretic acid inhibit DNA synthesis when added in early G1 phase [42].…”
Section: Nuclear Pla 2 Activitiesmentioning
confidence: 97%
“…49,50 We have shown that cPLA 2 activity increased transiently during mid-G1 phase of the ongoing cell cycle of CHO and neuroblastoma N2A cells, this activity being dependent upon the activity of p42/44. 51,52 By using different inhibitors of cPLA 2 , it was demonstrated that the activity of cPLA 2 in mid-G1 phase was required for entry into S phase. The effects of cPLA 2 inhibition on cell-cycle progression were mediated by lipoxygenase rather than cyclooxygenase products, because G1/S transition was only inhibited when lipoxygenase activity was prevented.…”
Section: A the Map Kinase Pathwaymentioning
confidence: 99%
“…The effects of cPLA 2 inhibition on cell-cycle progression were mediated by lipoxygenase rather than cyclooxygenase products, because G1/S transition was only inhibited when lipoxygenase activity was prevented. 52,53 In addition to the ERK1/2 pathways, MAP kinase homologs have been identified in mammalian cells such as the JNK/SAPK and the p38 HOG1 kinase. These MAP kinases respond to distinct extracellular stimuli and have different intracellular substrates.…”
Section: A the Map Kinase Pathwaymentioning
confidence: 99%